Sertifikasi Profesi Sebagai Strategi Penguatan Kompetensi Dan Scale Up Mitra UMKM Jasa Layanan Internet Studi Kasus Mitra ISP Datanet - Mochamad Sirodjudin (Universitas Yudharta Pasuruan, 2023)
This study aims to develop strategies of human quality improvement in internet services by providing training and professional certification especially MikroTik. And also provide guidelines about implementation in professional training and certification that can support the achievement of business scale up in internet services. The result is 19 out of 24 computer network administrators and technicians have successfully passed the certification and have the opportunity to take their competence to the next level. And from the results of discussions with trainers, several things that can be done to scale up is increasing the bandwidth gradually according to the turnover of each DataNet partner. Then periodically add access points in new areas that have potential markets. And what is no less important is gradually increasing the competence of computer network administrators and technicians because the level of difficulty and complexity of service is certainly different from before so that service to consumers is also getting better and improving.